Impact of integrative design on additive manufacturing quality. (1st January 2011) - Dietrich, David M.; Cudney, Elizabeth
To move additive manufacturing (AM) into a realm of credible manufacturing, quality evaluation techniques must be established to highlight the potential gains of AM technologies in the field of production quality in terms of dimensional control. This research aims to express the relationship among AM-enabled integrative design and quality evaluation techniques. The methodology proposed is backed by a comprehensive literature review that covers AM dimensional quality and conventional quality assessment techniques for production. The research proposes modelling the positive impact of integrating design using Taguchi's quality loss function (QLF) and tolerance stack-up models. In addition, the research provides a straightforward way to evaluate AM-enabled integrated designs that promotes the proliferation of AM technology as a sustainable and credible manufacturing method. A case study is presented that describes how to apply Taguchi's QLF to AM integrated designs.